2019
DOI: 10.1007/s11024-019-09381-6
|View full text |Cite
|
Sign up to set email alerts
|

The Patterning of Collaborative Behavior and Knowledge Culminations in Interdisciplinary Research Centers

Abstract: Due to investments in interdisciplinary research endeavors, the number and variety of interdisciplinary research centers have grown exponentially during the past decades. While interdisciplinary research centers rely on varied organizational arrangements, we know little about the conditions and processes that mediate collaborative arrangements and interdisciplinary research outcomes. This study examines how different collaborative arrangements shape scholars' experiences of interdisciplinary research and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Finally, the study found the physical space where the NRT program was housed and the structure of the NRT program acted as a sort of "third space" (O'Meara et al, 2018) or crossroads that facilitated regular engagement among students and faculty from different disciplines. Given technology has increased the likelihood for both graduate students and faculty to work from home and the fact that doctoral students from different disciplines areas "live" in different buildings across a large campusthis cross-roads space emphasize the importance of putting in place symbolic and concrete places where interdisciplinary connections can occur (Felt et al, 2013;Lyall and Meagher, 2012;Mäkinen et al, 2020). In other words, intentional NRT program activities nurtured meaningful collisions by allowing for exploration, encouraging students to share ideas and fostering engagement, rather than merely hoping that productive, interdisciplinary collisions would spontaneously occur by accident.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the study found the physical space where the NRT program was housed and the structure of the NRT program acted as a sort of "third space" (O'Meara et al, 2018) or crossroads that facilitated regular engagement among students and faculty from different disciplines. Given technology has increased the likelihood for both graduate students and faculty to work from home and the fact that doctoral students from different disciplines areas "live" in different buildings across a large campusthis cross-roads space emphasize the importance of putting in place symbolic and concrete places where interdisciplinary connections can occur (Felt et al, 2013;Lyall and Meagher, 2012;Mäkinen et al, 2020). In other words, intentional NRT program activities nurtured meaningful collisions by allowing for exploration, encouraging students to share ideas and fostering engagement, rather than merely hoping that productive, interdisciplinary collisions would spontaneously occur by accident.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, higher education institutions have made uneven progress on creating the infrastructure needed to support interdisciplinary collaboration. Some institutions adopted structures intended to facilitate interdisciplinary research (Holley, 2009a(Holley, , 2009bLindvig and Hillersdal, 2019;Lyall et al, 2015;Sá, 2008), such as building interdisciplinary centers, providing seed grants and recruiting interdisciplinary faculty (Holley, 2009a;Mäkinen et al, 2020;Müller and Kaltenbrunner, 2019;Sá, 2008). Other institutions created administrative roles geared at facilitating cross-unit research activities, developed cross-campus networks, and changed their missions to emphasize interdisciplinary collaboration as an institutional goal (Holley, 2009a;Sá, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, interdisciplinarity can also be similarly applied to understand the underlying complex mechanisms of few disciplines possible by merging their concept and perceptions ( Lindvig and Hillersdal, 2019 ). The term interdisciplinary as adjective is mainly confined to educational hubs to make the teaching learning system easy especially to make the pupils to understand the universal but subject specific events though muti-aided (from various subject specialities) pedagogy programs ( University of Texas, 2017 ; Mäkinen et al., 2019 ). For example, an on touched area of research in India is correlating between the haematology (blood cell pattern) and proteomics (study of proteins present in a particular community) of women from a particular race or community with any malfunctioned social activities such as their strong attitude to collect dowry during marriage and to torture newly married girls.…”
Section: Interdisciplinary Subjects and Need Based Researchmentioning
confidence: 99%
“…As such, more than ever before, researchers are expected to think and work across disciplines to solve pressing challenges (Ledford, 2015;Rylance, 2015;Andrews et al, 2020). Across the globe, interdisciplinary institutes and think tanks push innovation by facilitating knowledge exchange (Ledford, 2015;Vienni Baptista et al, 2019;Mäkinen et al, 2020). The European Union framework program Horizon 2020 has heavily promoted interdisciplinary research, even so far as stating that it is the "key to future scientific breakthroughs, " and awarded grants accordingly (Science Europe, 2012).…”
Section: Introductionmentioning
confidence: 99%